Cycle Threshold (CT) Values in COVID-19 Patients Admitted in Intensive Care Unit and Their Outcome: An Observational Study from South Punjab - Zohaib Ashraf, Amina Asif, Syed Khizar Abbas Rizvi, Uzma Shaheen, Muhammad Ilyas, Muhammad Daud Raza, Babar Abdul Ghafoor (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The World Health Organization declared the COVID-19 epidemic an international public health emergency on January 30th, 2020. Many patients required ICU admission for advanced respiratory support, including high flow nasal oxygen, and non‐invasive, and invasive mechanical ventilation. Lower Ct values may be associated with disease severity Objective: To observe the Cycle threshold (Ct) value and outcome of the COVID-19 patients admitted in Intensive Care Unit (ICU). Methods: Nasopharyngeal/ oropharyngeal samples were collected via swabs from suspected COVID-19-positive patients admitted to Corona ICU of Teaching Hospital, Dera Ghazi Khan (DG Khan). Samples were proceeded for RNA extraction and amplification and were declared positive on basis of the S-shaped amplification curve at FAM (ORF1) and ROX channel, and a Ct value of ≤40. Results: Out of 59 ICU admissions, 17 were females and 42 males. The highest percentage of mortality was observed in the 60 and above years of age group (78.98%). Ct values were lower in patients who expired as compared to the patients who were discharged (mean 21.052 vs 23.739). Conclusion: Males were more frequently admitted to ICU for management of severe infection by COVID-19 than females. Mortality is associated with increasing age. Cycle threshold (Ct) values were lower in patients who expired than those who recovered